Apoyo a la implementación de la ruta de reparación colectiva en proyectos de infraestructura social y comunitaria de la subdirección de reparación colectiva de la unidad para la atención y reparación integral a las victimas. Pasantía en el marco del programa gubernamental “estado joven”. (2021)
The majority of regions of Colombia that suffered the rigors of the armed conflict are impoverished regions, and in which the formulation of basic infrastructure projects is a huge challenge due to the lack of professional training of its inhabitants, however, in some cases with a lot of effort hiring local engineering consulting services, they manage to formulate studies and designs of social and community infrastructure projects that they present before the Unit for Comprehensive Care and Reparation to Victims to process collective reparation processes, through which they disburse resources, represented in construction materials and / or provision of furniture for the execution of these, in compliance with Law 1448 of the year 2011.